Effectiveness of Student Response Systems in secondary science education - Pfister, Meredith (My University, 2013)
This paper reports the findings of the effectiveness of Student Response Systems (SRS) in two ninth grade Physical Science classes. SRS are handheld devices given to each student so that they may respond to questions posed by the teacher during class. The teacher then uses the data from the responses to immediately guide their instruction. For this research, SRS were used for formative assessment for a two week unit of study in the test class but was not used in a control class studying the same material. Each class was given a pretest at the start of the unit and the same posttest at the end of the unit. After the units were finished, the test and control classes were swapped for another two week unit of study and pre and posttests were administered. No significant increases in posttest scores were found in the class using SRS compared to the class not using SRS for either unit. There was a noticeable increase in student engagement in class and students overwhelmingly preferred using SRS.
Plan B Paper. 2013. Master of Science in Education- Physics--University of Wisconsin-River Falls. Physics Department. 18 leaves. Includes bibliographical references (leaves 16-17).
Keywords: Student response systems; SRS; Science--Study and teaching (Secondary)